The Pilot Café launch - UiTM, UGC (UiTM Green Centre, 2025)
The launching ceremony of The Pilot Café at the College of Environmental Studies (KAB), UiTM Shah Alam, was successfully held in conjunction with the single-use plastic (SUP)-Free Community @ UiTM Program. Initiate by the UiTM Green Centre (UGC) with support from Shah Alam City Council (MBSA) through strategic partnership funding, this program is part of UiTM’S efforts to reduce plastic waste and promote campus sustainability.